Strategi Keberlangsungan Bisnis Dalam Menghadapi Pandemi Covid-19 - Afifah Rida Salsabila; Hilda Rossieta (Politeknik Ganesha Medan, 2023)
This study aims to understand the impact of the Covid-19 crisis on food and beverage companies and the business continuity strategies carried out by the companies to address the crisis. This study uses case study research with a qualitative approach. The data used in this study is secondary data collected from the chosen sample of food and beverage companies listed on the Indonesian Stock Exchange (IDX) in the form of annual reports, public exposure, news, and other public information during the time of crisis in 2020 and 2021. Sampling was conducted on 18 companies listed in the food and beverage sector on IDX that experienced negative sales in 2020 and 2021. Afterward, clustering was carried out on these companies into three categories based on market capitalization. From each market capitalization category, one company with the highest negative sales rate was selected for analysis. This study unveils that the Covid-19 crisis had a significant impact on each of the companies, not only seen in financial aspects but also in non-financial aspects. The impact of the Covid-19 crisis encourages companies to formulate new strategies to address the crisis and preserve their business continuity, even if they have to change the entire business model